Making Recruitment and Selection Tools to Solve the Lack of Human Resources in Benchmark Company - Bella Halim (Institute of Research and Community Outreach - Petra Christian University, 2019)
Benchmark is the parent company of Basha Market and Of Sorts. The main problem of Benchmark is a lack of human resources. In their new organizational structure, there are still seven vacant positions in their three departments. New qualified employees are needed to fill these positions. In order to do that, recruitment and selection tools are needed. The first tool, the recruitment tools, can help Benchmark attract the right people for the jobs. They consist of job advertisements and an application form. The second tool, the selection tools, can help the company screen the candidates to finally pick the best people to work for them. The tools consist of a pre-interview questionnaire and the an interview question sheet. With all the tools, Benchmark can select the right candidates and expected to be able to function as an effective and efficient company to deal with future challenges. Keywords: Hiring, Recruitment, Selection, Human Resources, Job Description.